Manufacturing & distribution U.S.A. industry analyses, statistics, and leading companies. - Darnay, Arsen; Gale Group (Detroit, Mich. : Gale Group, 2009)
Presents statistics on numerous NAICS classifications in the manufacturing, wholesaling and retail industries. Compiled from the most recent government publications. Covers input-output data by industrial sector when available as well as classifications of leading public and private corporations in each industry.
Ηλεκτρονικό βιβλίο
Keywords: Manufacturing industries -- United States -- Statistics -- Periodicals; Industries -- United States -- Statistics -- Periodicals; Distributors (Commerce) -- United States -- Statistics -- Periodicals; Electronic books